2010
DOI: 10.1186/1471-2458-10-444
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists' involvement in smoking cessation: familiarity and implementation of the National smoking cessation guideline in Finland

Abstract: BackgroundGuidelines on smoking cessation (SC) emphasize healthcare cooperation and community pharmacists' involvement. This study explored the familiarity and implementation of the National SC Guideline in Finnish community pharmacies, factors relating to Guideline familiarity, implementation and provision of SC services.MethodsA nationwide mail survey was sent to a systematic, sample of community pharmacy owners and staff pharmacists (total n = 2291). Response rate was 54% (n = 1190). Factors related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…This finding is consistent also with previous research on the familiarity of the current care guideline on smoking cessation among community pharmacists in Finland: 47% of the respondents were familiar with the guideline 4 years after its’ original publication and 1 year after its update in 2007. 27 Similarly, a study from England found that the local current care guideline or COPD management was read by approximately 47% of community pharmacists. 28 …”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent also with previous research on the familiarity of the current care guideline on smoking cessation among community pharmacists in Finland: 47% of the respondents were familiar with the guideline 4 years after its’ original publication and 1 year after its update in 2007. 27 Similarly, a study from England found that the local current care guideline or COPD management was read by approximately 47% of community pharmacists. 28 …”
Section: Discussionmentioning
confidence: 99%
“…As community pharmacists are in locations where patients could easily access, evidence in many countries has shown the success of smoking cessation services provided by community pharmacists [ 8 , 9 ]. Smoking cessation services were provided by health care workers, including pharmacists in many countries, such as in the UK, USA, Finland, as well as Thailand [ 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since almost half of the respondents showed to have a poor knowledge, there is a need for an increase in awareness among pharmacists about COPD (particularly clinically related guidelines) and better counseling that should be more patient oriented. This is supported by several studies where it was shown that pharmacists as well as other health-care providers who were aware of the current care guideline or participated in learning activities used the information more extensively for the benefit of the patients [45,47,59]. In addition, a systematic review showed that community pharmacists can successfully screen patients at risk of COPD and have a positive impact on those patients [60].…”
Section: Practice Implications and Future Studiesmentioning
confidence: 77%
“…Other reported studies in Europe identified that the level of knowledge is suboptimal. Therefore, continuing education must be implemented to help pharmacists cope with the new guidelines and above all know how to transfer this knowledge into evidence-based counseling [47,48].…”
Section: Multivariable Analysismentioning
confidence: 99%